Assessment of animal diseases caused by bacteria resistant to antimicrobials: cattle. (10th December 2021) - ,; Nielsen, Søren Saxmose; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortazar Schmidt, Christian; Herskin, Mette; Michel, Virginie; Miranda Chueca, Miguel Angel; et al.
Abstract: In this opinion, the antimicrobial resistant bacteria responsible for transmissible diseases that constitute a threat to the health of cattle have been assessed. The assessment has been performed following a methodology based on information collected by an extensive literature review and expert judgement. Details of the methodology used for this assessment are explained in a separate opinion. A global state of play on antimicrobial resistance in clinical isolates of Escherichia coli (non‐VTEC), Klebsiella pneumoniae, Staphylococcus aureus, Streptococcus uberis, Streptococcus dysgalactiae, Pasteurella multocida, Mannheimia haemolytica, Histophilus somni, Mycoplasma bovis, Moraxella bovis, Fusobacterium necrophorum and Trueperella pyogenes is provided. Among those bacteria, EFSA identified E. coli and S. aureus with ≥ 66% certainty as being the most relevant antimicrobial resistant bacteria in cattle in the EU based on the available evidence. The animal health impact of these most relevant bacteria, as well as their eligibility for being listed and categorised within the animal health law framework will be assessed in separate scientific opinions.